1997
DOI: 10.1210/endo.138.9.5395
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Variation in Basal Plasma Corticosterone and Adrenocorticotropin in the Rat: Sexual Dimorphism and Changes across the Estrous Cycle*

Abstract: Sexual dimorphism in the rat hypothalamic-pituitary-adrenal axis was investigated by determination of plasma corticosterone and immunoreactive (I-) ACTH in males and in females at each stage of the estrous cycle. A serial blood-sampling technique enabled assessment of covariation of the two hormones across the full circadian range of their concentrations within individual animals. Distinct diurnal rhythms in plasma corticosterone were evident in all rats, and the degree and timing of this rhythmicity, determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(52 citation statements)
references
References 44 publications
4
44
0
Order By: Relevance
“…This apparent decoupling of circulating ACTH and corticosterone suggests that factors outside the conventional HPA axis influence plasma corticosterone in pregnancy. For example, enhanced adrenal responsiveness appears to drive increased maternal corticosterone levels after mid-gestation in the rat (Atkinson & Waddell 1995), an effect likely mediated via rising estrogen levels (Atkinson & Waddell 1997, Figueiredo et al 2007). Other 'non-HPA axis' factors that could enhance maternal levels of corticosterone include a fall in its metabolic clearance rate due to higher plasma corticosteroid-binding globulin (CBG) levels (Gala & Westphal 1967, Douglas et al 2003 or a contribution from the fetal adrenal.…”
Section: Discussionmentioning
confidence: 99%
“…This apparent decoupling of circulating ACTH and corticosterone suggests that factors outside the conventional HPA axis influence plasma corticosterone in pregnancy. For example, enhanced adrenal responsiveness appears to drive increased maternal corticosterone levels after mid-gestation in the rat (Atkinson & Waddell 1995), an effect likely mediated via rising estrogen levels (Atkinson & Waddell 1997, Figueiredo et al 2007). Other 'non-HPA axis' factors that could enhance maternal levels of corticosterone include a fall in its metabolic clearance rate due to higher plasma corticosteroid-binding globulin (CBG) levels (Gala & Westphal 1967, Douglas et al 2003 or a contribution from the fetal adrenal.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, sleep occurs during periods of the diurnal rhythm when CORT levels are reduced (28,29). However, several lines of evidence argue against this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that rats show a strong preference for solid floor compared with grid floor cage (38). Other studies show that housing rats on grid floor cages induce tactile hypersensitivity and nerve injury in the hind feet (39) and can also increase plasma level of corticosterone, blood pressure, heart rate and body temperature (40). Thus, this housing condition could alter faecal hormone metabolite assessment in rats.…”
Section: Discussionmentioning
confidence: 99%